Psychometric properties of the parent's versions of the SDQ and the PANAS-X in a community sample of Portuguese parents. (April 2020) - Costa, Pedro Alexandre; Tasker, Fiona; Ramos, Catarina; Leal, Isabel
This study examined the psychometric properties of the parent's versions of the Strengths and Difficulties Questionnaire (SDQ) and the Positive and Negative Affect Schedule–Extended Form (PANAS-X) in a community sample of Portuguese parents. A total of 1100 SDQ and PANAS-X were collected from an online sample of 761 parents, whose ages ranged from 23 to 65 years ( M = 42, SD = 5). Confirmatory factor analyses provided evidence of the internal factor structure of both the SDQ and the PANAS-X and invariance of the factor structure across age and gender groups, with the exception of the SDQ, which failed to provide evidence of invariance between genders. Internal reliability and discriminant validity were confirmed for both measures, although convergent validity was only confirmed for the PANAS-X. Concurrent validity was also confirmed by comparing the results from the SDQ dimensions and the PANAS-X broad dimensions subscales.